2016
DOI: 10.1155/2016/6487509
|View full text |Cite
|
Sign up to set email alerts
|

CD36/Sirtuin 1 Axis Impairment Contributes to Hepatic Steatosis in ACE2‐Deficient Mice

Abstract: Background and Aims. Angiotensin converting enzyme 2 (ACE2) is an important component of the renin-angiotensin system. Since angiotensin peptides have been shown to be involved in hepatic steatosis, we aimed to evaluate the hepatic lipid profile in ACE2-deficient (ACE2−/y) mice. Methods. Male C57BL/6 and ACE2−/y mice were analyzed at the age of 3 and 6 months for alterations in the lipid profiles of plasma, faeces, and liver and for hepatic steatosis. Results. ACE2−/y mice showed lower body weight and white ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…Consequently, PGC-1α can interact with nuclear receptors PPARα, estrogen-related receptor alpha (ERRα), and HNF4α to promote mitochondrial FAO [52,54,55]. Accordingly, hepatocyte deletion of SIRT1 diminishes the expression of β-oxidation genes, increases fasting-induced lipid accumulation in the liver, and triggers diet-induced steatosis [56,57]. However in the fed state, insulin stimulates PGC-1α phosphorylation by Akt, which impairs the capacity of PGC-1α to trigger fatty acid β-oxidation [33].…”
Section: Tissue-specificmentioning
confidence: 99%
“…Consequently, PGC-1α can interact with nuclear receptors PPARα, estrogen-related receptor alpha (ERRα), and HNF4α to promote mitochondrial FAO [52,54,55]. Accordingly, hepatocyte deletion of SIRT1 diminishes the expression of β-oxidation genes, increases fasting-induced lipid accumulation in the liver, and triggers diet-induced steatosis [56,57]. However in the fed state, insulin stimulates PGC-1α phosphorylation by Akt, which impairs the capacity of PGC-1α to trigger fatty acid β-oxidation [33].…”
Section: Tissue-specificmentioning
confidence: 99%
“…Since then, this line has been widely used in a variety of disease models. Overall, these studies reveal that ACE2 is protective against Ang-II-mediated or pressure overload-induced heart failure 23,24 , myocardial infarction 25 , vascular dysfunction and atherosclerosis 26,27 , abdominal aortic aneurysm 28 , hepatic steatosis and fibrosis 29,30 , obesity or diabetes-associated metabolic and cardiovascular disorders 31,32 , renal fibrosis and inflammation 33,34 , and diabetes or hypertension associated nephropathy 35,36 . Separate from ACE2's functions in the counterbalance of Ang-II/AT 1 R signaling, studies using this KO line also identified an association between ACE2 and the amino acid transporter B 0 AT1, and deletion of Ace2 leads to reduced intestinal uptake of tryptophan and altered serotonin metabolism 37,38 .…”
Section: Global Ace2 Ko Modelsmentioning
confidence: 99%
“…Canada Cardiovascular: Enhanced susceptibility to Ang-II or pressure overload-induced heart failure 23,24 , cardiac hypertrophy and myocardial fibrosis 14 , myocardial infarction 25 , vascular dysfunction and atherosclerosis 26,27 , abdominal aortic aneurysm 28 Metabolic: Lipodystrophy and steatosis 29 , obesity-induced epicardial adipose tissue inflammation and insulin resistance 31 , diabetic cardiovascular complications 32 , reduced intestinal uptake of tryptophan and altered serotonin metabolism 37,38 Liver: Hepatic steatosis and fibrosis 29,30 Lung: Resistant to SARS-CoV infection 39 , exacerbated ALI/ARDS due to acid aspiration, lipopolysaccharide or pseudomonas aeruginosa infection [41][42][43] , impaired inactivation of des-Arg 9 -bradykinin 43 , exacerbated lung fibrosis with a sex dichotomy 44 , increased susceptibility to respiratory viral infection [45][46][47] Kidney: Renal fibrosis and inflammation 33,34 and diabetes or hypertension associated nephropathy 35,36 Life Science Institute, The University of British Columbia USA 1. Developmental: Gestational impairment in Ace2 −/− dams 50,51 , smaller size and slower to develop 48,49 Cardiovascular: Mild elevation of systolic BP 15 , enhanced Ang-II-induced hypertension 15 and myocardial dysfunction 52 , diet or diabetes-associated hypertension 48,53 , increased susceptibility to atherosclerotic plaques 55 , autonomic dysfunction and increased oxidative stress …”
Section: Phenotypes Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…24 hours later, behavioral tests were carried out in separate animal groups 1 . Euthanasia was conducted by decapitation under xylazine/ketamine anesthesia 15 .…”
Section: Experimental Designmentioning
confidence: 99%